Prevalence and quantification of Listeria monocytogenes in chicken offal at the retail level in Malaysia. - Kuan, Chee Hao; Goh, Sur Guat; Loo, Yuet Ying; Chang, Wei San; Lye, Ying Ling; Soopna, Puspanadan; Tang, John Yew Huat; Nakaguchi, Yositsugu; Nishibuchi, Mitsuaki; Mahyudin, Nor Ainy; Radu, Son (Oxford University Press, 2013)
A total of 216 chicken offal samples (chicken liver = 72; chicken heart = 72; chicken gizzard = 72) from wet markets and hypermarkets in Selangor, Malaysia, were examined for the presence and density of Listeria monocytogenes by using a combination of the most probable number and PCR method. The prevalence of L. monocytogenes in 216 chicken offal samples examined was 26.39%, and among the positive samples, the chicken gizzard showed the highest percentage at 33.33% compared with chicken liver (25.00%) and chicken heart (20.83%). The microbial load of L. monocytogenes in chicken offal samples ranged from <3 to 93.0 most probable number per gram. The presence of L. monocytogenes in chicken offal samples may indicate that chicken offal can act as a possible vehicle for the occurrence of foodborne listeriosis. Hence, there is a need to investigate the biosafety level of chicken offal in Malaysia.